2004
DOI: 10.1242/jcs.01093
|View full text |Cite
|
Sign up to set email alerts
|

Retention and stimulus-dependent recycling of dense core vesicle content in neuroendocrine cells

Abstract: We have used fluorescence imaging of individual exocytic events in combination with immunogold electron microscopy and FM1-43 photoconversion to study the stimulus-dependent recycling of dense core vesicle content in isolated rat pituitary lactotrophs. Secretory stimulation with high external [K+] resulted in 100 exocytic sites per cell that were labeled by extracellular antibodies against the peptide hormone prolactin. Morphological analysis demonstrated that the prolactin was retained and internalized in int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
1

Year Published

2004
2004
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 64 publications
5
35
1
Order By: Relevance
“…Together, our results indicate that after secretion the prolactin that remains associated with the cells is internalized and sorted to a secretory compartment, processes that imply its functional recycling. Although these findings are in agreement with the observations by others (34), it remains to be established whether functional recycling of unspent post-exocytotic hormone is peculiar to prolactin or a phenomenon common to other regulated secretory peptides.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Together, our results indicate that after secretion the prolactin that remains associated with the cells is internalized and sorted to a secretory compartment, processes that imply its functional recycling. Although these findings are in agreement with the observations by others (34), it remains to be established whether functional recycling of unspent post-exocytotic hormone is peculiar to prolactin or a phenomenon common to other regulated secretory peptides.…”
Section: Discussionsupporting
confidence: 89%
“…It has been reported recently that, upon stimulation with high K ϩ at 22°C, prolactin cores remain associated with the plasma membrane, undergo internalization, and following restimulation, reappear at the cell surface (34). We found that in resting conditions 10% of the total prolactin was biotinylated in 30 min at 37°C, signaling its appearance at the cell surface.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Instead of granule collapse, fusion pore opening can be followed by closure. A final closure of the fusion pore is an essential step in the kiss-and-run model of exocytosis (Ceccarelli et al, 1972), where it is the transitional step between exocytosis and the endocytic recovery of the granule (Holroyd et al, 2002;Bauer et al, 2004;Tsuboi et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…1B). Significantly these recaptured vesicles can contain residual quantities of peptide hormones [13][14][15] suggesting that fusion pore dynamics is a limiting factor in the release of peptides. Some papers now suggest that fusion pore dynamics might specifically regulate the loss of low molecular weight (<200 Da) neurotransmitters.…”
Section: Graded Secretion As a New Model For Secretory Controlmentioning
confidence: 99%